MORALITY AND SOCIAL ASSISTANCE IN SCHOOLS - Bucky Wibawa Karya Guna; Hosaini; Sri Haryanto; Haya; M. Fathun Niam (International Journal of Teaching and Learning, 2024)
This research deals with morality and social deviations with emphasis on basic moral concepts, deviant behavior, the role of students in deviant conduct, and the school's role in shaping children's behaviour. The study examines the factors that influence behavior and interpersonal relationships and provides insight into how to reduce bad behaviour. This research uses a qualitative approach by reviewing relevant literature and research in this field. The results of this research show that the main concept of morality encompasses the moral principles that shape values and norms in society. Asusile behavior includes behaviors that violate social norms and can have a negative impact on individuals and societies. Students are often susceptible to behavioral disorders due to various factors such as peer stress, social media influence and the environment. However, schools can play an important role in shaping child behavior through structured behavioral instruction, value-based learning approaches, and social development. Collaborative efforts between schools, families and communities are also needed to resolve moral conflicts and encourage strong behavior in the younger generation.